Sustainability assessment of Thailand's electricity planning: Using section 1 of the 2009 hydropower sustainability assessment protocol - Foran, T.; Resurrección, Bernadette P.; Kansantisukmongkul, C.; Wirutskulshai, U.; Leeruttanawisut, K.; Lazarus, Kate (Australian Government Aid Program, M-POWER and CGIAR Challenge Program on Water and Food, 2010)
We conducted a rapid assessment of the sustainability performance of the Thai power development plan and a number of related planning processes, focusing on the Thai plan’s implications for development of hydropower in the Mekong region. We used the August 2009 draft Hydropower Sustainability Assessment Protocol (HSAP), which is a qualitative multi-criteria audit tool designed to be used by a wide range of interested parties. We applied the HSAP from a public interest perspective: We assumed that aquatic ecosystems in the Mekong region are critically important for less privileged people, and that Thailand’s electricity planners can and should consider the distributional and ecological consequences of planning choices on a Mekong regional scale.